Shape memory alloys applications on weft knitted fabrics towards a compression sock for venous disease - Pereira, F. R. (2017)
Shape Memory Alloys (SMA) are currently widely used in several areas, and it is possible to identify applications in textiles. Nevertheless there still are areas where they can be applied with success, and one of them may be the compression. The study that is presented here intends to contribute for a better understanding about the behaviour of SMA in textile structures, namely on weft knitted fabrics. Different structures were produced together with different loop lengths for a specific SMA and then mechanically characterized and observed towards the development of a sock with SMA filament embedded which was then characterized.